Implications of food trade policy for domestic and international food price volatility - Martin, Will; Mamun, Abdullah; Minot, Nicholas (CGIAR System Organization, 2025)
This paper investigates the impact of food trade policies on domestic and international price volatility, focusing on rice and wheat markets. It posits that policymakers aim to minimize the political costs associated with changing domestic prices and those associated with deviating from political-economy equilibria. The study uses price data, adjusted to reflect trade costs, to estimate an Error Correction Model that identifies key policy response parameters. The findings suggest that systematic, short-run protection changes designed to insulate against changes in world prices reduce shocks to domestic prices but exacerbate world price volatility. However, idiosyncratic, national shocks to protection rates—such as those due to national weather shocks—increase domestic price volatility relative to the amplified volatility of world prices. Our findings challenge the conventional view of price insulation as a zero-sum game, suggesting it is a negative-sum game that increases domestic price volatility for almost all countries, creating opportunities for policy reforms to lower costs and reduce price volatility.